DNA metabarcoding reveals the influence of land cover and farming on the dietary composition of a spider-specialist bat - Nerea Vallejo; Miren Aldasoro; Lander Olasagasti; Joxerra Aihartza; Inazio Garin (Metabarcoding and Metagenomics)
Human-driven landscape transformations are the primary factors driving biodiversity changes in the present century. For insectivorous bats, land-use modifications and intensification of agriculture negatively impact bat foraging activity and, consequently, the potential ecosystem services they can provide. However, little is known about specific dietary niche adaptations to anthropogenic land changes. Here, we analysed the influence of land cover and agricultural practices, especially livestock, on the diet of the notch-eared bat. We collected faecal samples from sixteen maternity colonies in the Iberian Peninsula and southern France during two different sampling periods, May and July of 2020. We analysed 318 faecal samples using DNA metabarcoding, resulting in 241 identified prey species. Spiders were the most consumed prey item, followed by livestock pest flies (Muscidae). Dietary diversity was higher in May, while the weighted percentage of occurrence (wPOO) of spiders was higher in July. Consumption of harmful livestock pests was more likely in areas where livestock were prevalent near the colony; however, other landscape characteristics such as forest cover and urban areas had a greater influence on the wPOO values of pests. Our results highlight the consistency of the dietary composition of the notch-eared bat across large geographical areas, and its reliance on gleaning for hunting motionless prey. The interaction between livestock farming densities, livestock management types and land use around the colony will influence the densities of pest flies and other arthropods, ultimately shaping the trophic niche of M. emarginatus.